Exploring language assessment and testing : language in action - Green, Anthony, 1966- (Routledge introductions to applied linguistics, 2021)
"The Routledge Introductions to Applied Linguistics series takes an innovative 'practice to theory' approach, with a 'back-to-front' structure. This leads the reader from real-world problems and issues, through a discussion of intervention and how to engage with these concerns, before finally relating these practical issues to theoretical foundations. Exploring Language Assessment and Testing offers a straightforward and accessible introduction that starts from real-world experiences and uses practical examples to introduce the reader to the academic field of language assessment and testing. Extensively updated, with additional features such as reader tasks (with extensive commentaries from the author), a glossary of key terms and an annotated further reading section, this second edition provides coverage of recent theoretical and technological developments and explores specific purposes for assessment. Including concrete models and examples to guide readers into the relevant literature, this book also offers practical guidance for educators and researchers on designing, developing and using assessments. Providing an inclusive and impartial survey of both classroom-based assessment by teachers and larger-scale testing, this is an indispensable introduction for postgraduate and advanced undergraduate students studying Language Education, Applied Linguistics and Language Assessment"--